2013
DOI: 10.1177/2042533313497183
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of proton pump inhibitors among medical inpatients: a questionnaire-based observational study

Abstract: ObjectivesTo evaluate the appropriateness of proton pump inhibitor (PPI) prescribing by conducting an audit of medical inpatients against recommended guidelines.DesignQuestionnaire-based study. All medical wards were audited and different information was documented by patients' medical records review (both hospital visit notes and general practitioner's letters) and short interview, where we asked them to name the clinical reason for using PPI.SettingThis study was carried out in the setting of a regional hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…20 Other recent studies have shown that physicians do not review and document PPI indications in a large number of cases, which often results in their long-term or even indefinite continuation. 1,19,20 This is of interest because even among the 16 patients in our study with newly prescribed PPI prescriptions at discharge, only two patients were discharged with any documented justification.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Other recent studies have shown that physicians do not review and document PPI indications in a large number of cases, which often results in their long-term or even indefinite continuation. 1,19,20 This is of interest because even among the 16 patients in our study with newly prescribed PPI prescriptions at discharge, only two patients were discharged with any documented justification.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
“…However, all recent studies have reported a very high prevalence of inappropriate PPI prescribing and our result findings are consistent with these studies. 2,3,4,[18][19][20] Finally, as the guidelines recommend periodic assessment for the continued use of PPI, it may be challenging to assess symptoms among the very elderly, frail, and debilitated elderly with dementia and communication issues. This may have posed difficulties for the prescribing physicians in determining the need for a prescription.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
“…5 The aim was to evaluate the appropriateness of PPIs prescription by conducting an audit against recommended guidelines (NICE 2000).…”
Section: Overutilization Of Proton Pump Inhibitors Therapy In Hospitamentioning
confidence: 99%
“…Prethodni pepički ulkus ili kardiogeni šok su bili značajni nezavisni faktori rizika. Istovremena primena IPP značajno redukukuje rizik 5,[20][21][22] .…”
Section: Anikoagulantna Terapijaunclassified